GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PERAWATAN DAN STIMULASI TUMBUH KEMBANG BAYI USIA 0-6 BULAN - Puspa Kusumaningsih, Tri; Khalishah Huda, Dzakiyyah; Fitriana Agustin, Malikah (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
Background: Parents play a very important role in the process of children's growth and development in meeting adequate nutritional needs, providing attention and affection, and providing stimulus to help the process of perfecting the child's nervous tissue. Based on a preliminary study conducted in March – August 2023 at the Semawung Daleman Health Center, Kutoarjo District, Purworejo Regency, the results of interviews with 10 mothers regarding mothers' knowledge regarding care and growth and development stimulation, there were 5 respondents who had good knowledge, 2 respondents had sufficient knowledge, and 3 respondents do not know. Research Objective: to find out the description of mothers' knowledge about caring for and stimulating growth and development in babies aged 0-6 months at the Semawung Daleman Community Health Center, Purworejo Regency. Research method: Qualitative descriptive, research instrument using a checklist. The number of respondents was 54 respondents, using the Accidental Sampling technique Research Results: Most respondents (66.7%) had a good level of knowledge, and a small percentage (14.8%) of respondents had a sufficient level of knowledge about caring for and stimulating the growth and development of babies aged 0-6 months. Conclusion: Based on the research results, the majority of toddler mothers' knowledge level is sufficient regarding the care and stimulation of growth and development of babies aged 0-6 months. Suggestion: It is hoped that health workers will be more intensive in providing education about the care and growth and development stimulation of babies 0-6 months